Impact of Venous Thromboembolism on the Formation and Progression of Carotid Atherosclerosis: The Tromsø Study - Lind, Caroline; Småbrekke, Birgit; Rinde, Ludvig Balteskard; Hindberg, Kristian; Mathiesen, Ellisiv Bøgeberg; Johnsen, Stein Harald; Arntzen, Kjell Arne; Njølstad, Inger; Lijfering, Willem; Brækkan, Sigrid Kufaas; Hansen, John-Bjarne (TH Open, 2017)
Venous thromboembolism (VTE) is associated with increased risk of arterial cardiovascular diseases (CVD), and development of atherosclerosis secondary to VTE may be an intermediate between VTE and CVD. Therefore, we aimed to investigate whether incident VTE was associated with subsequent carotid atherosclerosis formation and progression in a population-based observational study. Subjects attending two or more ultrasound examinations of the right carotid artery, with measurement of total plaque area (TPA), in the Tromsø Study in 1994–1995, 2001–2002, and/or 2007–2008 were eligible. We identified 150 subjects diagnosed with first-lifetime VTE between the initial and follow-up visit, and randomly selected 600 age- and sex-matched subjects without VTE between the visits. Subjects with VTE and carotid plaque(s) at the first visit had 4.1 mm2 (β: 4.13, 95% CI: −1.72 to 9.98) larger change in TPA between the first and second visit compared with subjects without VTE after adjustment for change in high-sensitivity C-reactive protein (hs-CRP) and traditional atherosclerotic risk factors. The association remained after restricting the analyses to VTE events diagnosed in the first half of the time interval between the carotid ultrasounds (β: 4.02, 95% CI: −3.66 to 11.70), supporting that the change in TPA occurred subsequent to the VTE. No association was found between VTE and novel carotid plaque formation. In conclusion, we found a possible association between VTE and atherosclerosis progression in those with already established carotid plaques, but not between VTE and novel plaque formation. The association between VTE and carotid plaque progression was not mediated by low-grade inflammation assessed by hs-CRP.
Keywords: atherosclerosis; epidemiological studies; risk factors; venous thrombosis